THE ROLE OF BRAND IMAGE AS A MEDIATION OF THE INFLUENCE OF PRODUCT PRICE AND QUALITY ON PURCHASE DECISION: Study of "Collapsed" Beef Consumers in Jombang - Yaqin, Mohammad Nurul; Askafi, Eka; Arisyahidin, Arisyahidin (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2023)
This research aims to determine whether the product's Price and quality influence the brand image and purchasing decisions of collapsed beef among residents in Jombang Regency. This study uses a quantitative approach. The population in this study was Jombang residents, while the sample used was 100 people, determined using the Slovin formula. This research uses primary data obtained through distributing questionnaires. The analytical tool used is influenced by the Price and quality of the product, which influences the brand image of collapsed beef, to find out how Price, product quality, and brand image influence the decision to purchase collapsed beef and to find out whether the brand image can mediate the influence of price and product quality on beef purchasing decisions collapse. The method used in this research is a survey method, where the author distributes questionnaires for data collection. The approach used in this research is quantitative. Data analysis using smartPLS SEM software. The research results show that Price has a positive contribution to brand image, while product quality does not contribute to brand image. Apart from that, Price also contributes positively to purchasing decisions. However, product quality does not contribute to purchasing decisions. The brand image also influences purchasing decisions. Brand image can partially mediate price influence on purchasing decisions but cannot influence product quality.